Trends in single trait dispersion between early-mid successional stages: the importance of species pool extension and habitat scale. (2nd December 2016) - Gafta, Dan; Roman, Anamaria; Ursu, Tudor M
Abstract: Aims: Are there trends of increasing/decreasing dispersion of single, categorical traits related to early/late-successional species between stages of community development? If yes, are these trends dependent on species pool extension and habitat scale? Is there a consistent reduction in single trait convergence or divergence in any seral stage when scaling down from ecological to local species pool? Methods: Presence of all vascular species rooted within plots of 5 × 5 m was recorded in assemblages of exposed mining spoils (EMS) and heathlands (HTL), which form a chronosequence on two abandoned ore tailing heaps located close to each other in the south-eastern Carpathians (Romania). Fifteen nominal, trait attributes of plant species co-occurring in the two seral assemblages were collected from available databases and subsequently classified as either successionally 'pioneer' or 'mature'. The strength of single trait convergence or divergence was estimated by comparison with null plant assemblages at patch type (meta-community) level by reference to the ecological or local species pool, and at community level. Important Findings: At patch type level, all pioneer and mature trait attributes (apart from short life span), with significant variation between the two seral stages, increased and, respectively, decreased in dispersion irrespective of species pool extension. However, these trends were more conspicuous when using the ecological species pool, very likely due to relaxation in abiotic filtering and dispersal limitation. At community level, no consistent trends were observed between EMS and HTL assemblages, probably because most trait attributes were sorted by microenvironmental filters displaying high variation, like topography or habitat patch geometry. In both seral stages, there was a general weakening of trait convergence or divergence at patch type level when scaling down from the ecological to the local species pool, which was due to niche space contraction. At community level, there was a trend of rise in dispersion of pioneer attributes along the observed chronosequence, presumably imputable to increasing competition for light and underground water, but an opposite trend of dispersion drop in mature attributes was not so evident. Based on these findings, we proposed two rules of thumb concerning the expected changes in dispersion of trait attributes at patch level along successions and between levels of species pool extension. In conclusion, trends in the successional dynamics of pioneer and mature trait dispersion are clearly detectable at meta-community level, especially by reference to the ecological species pool. Habitat scale and species pool extension are key factors to consider and report when estimating the magnitude of single trait dispersion.